Black Hole Quenchers for SERRS Imaging of CXCR4 Expression at Single‐Cell Level During Treatment - Zhu, Congzheng; Li, Jin; Chen, Xinru; Fu, Longwen; Zhang, Zhiyang; Wang, Yunqing; Wang, Xiaoyan; Chen, Lingxin (Advanced functional materials, 2025)
CXC chemokine receptor 4 (CXCR4) is recently regarded as a valuable biomarker for triple‐negative breast cancer (TNBC) metastasis but lacks available imaging reagents. Surface‐enhanced resonance Raman scattering (SERRS) with resonant dyes has emerged as a powerful tool for single‐cell imaging because of the electronically enhanced vibrational fingerprint signals. However, resonant Raman signals are often overwhelmed by accompanying fluorescence backgrounds. To address this, two black hole quenchers (BHQs) are designed as visible resonance Raman reporters with absolutely nonfluorescent readouts. Ultrafast spectroscopy elucidates that the nonfluorescent mechanism of the reporters originates from the ultrafast internal conversion at the subpicosecond scale that quenches the excited states of fluorescence. SERRS nanoprobes (NPs) decorated with such reporters exhibit strong Raman enhancement (5.82 × 106), the femtomolar‐level limit of detection as well as unrivaled photostability (τs = 26516 s), outperforming that of crystal violet‐decorated counterparts. When conjugation of a CXCR4 antagonist, these fluorescence‐free SERRS NPs allow for photostable imaging of CXCR4 on TNBC cells at the single‐cell level, and for monitoring the expression variation during combined drug treatment. To the best of the available knowledge, this is the first example of absolutely nonfluorescent Raman reporters for single‐cell SERRS imaging. Black hole quenchers (BHQs) based nonfluorescent resonant Raman reporters are presented for the first time. BHQ‐based Raman nanoprobes exhibit excellent SERRS performance and unparalleled photostability. When conjugated with a CXCR4 antagonist, these nonfluorescent SERRS nanoprobes allow for photostable imaging of CXCR4 expression of triple‐negative breast cancer cells at the single‐cell level during single‐drug and multi‐drug treatment.